The Implementation of the community language learning (CLL) method to improve the listening and speaking skills of Arabic of class VIII students at the Al-Faruqi Kampar Islamic boarding school - Layyinatil Awaliyah; Promadi Karim; Masrun Masrun (Jurnal Pendidikan Educandum, 2025)
This experimental research uses a quantitative approach, which aims to determine whether there is a significant difference between the experimental class and the control class in improving the listening and speaking skills of class VIII students in Al-Faruqi Kampar Islamic Boarding School. The formulation of the problem in this study is "Is there a significant difference between the experimental class and the control class in improving the listening and speaking skills of class VIII students in Al-Faruqi Kampar Islamic Boarding School?". The population in this study was all class VIII students at the Al-Faruqi Kampar Islamic Boarding School in the 2024/2025 academic year, while the sample in this study was 44 students in class VIII 1 and VIII 2. Data collection using observation and tests. Based on the results of data analysis on listening skills, the value of to = 5.69% is greater than tt at a significance level of 1% (2.02) and a significance level of 5% (2.72), and on speaking skills the value of to = 6.67% is greater than tt at a significance level of 1% (2.02) and a significance level of 5% (2.72). So Ho is rejected and Ha is accepted, namely there is a significant difference between the experimental class and the control class in improving the listening and speaking skills of Arabic students in grade VIII at the Al-Faruqi Kampar Islamic Boarding School, so that the community language learning method is declared effective in improving the listening and speaking skills of grade VIII students at the Islamic Boarding School Al-Faruqi Kampar.